ANALISIS PERUBAHAN CURRENT RASIO PADA PT. ULTRA JAYA SEBELUM, SAAT, SETELAH PANDEMI COVID-19 - Anastasia, Cindy; Wijaya, Lauren; Manurung, Elizabeth Tiur (Jurnal Akuntansi Kompetif, 2025)
This research aims to analyze changes of the current ratio of leading dairy industry company in Indonesia, namely PT. Ultra Jaya Milk Industry And Trading Company, Tbk before, during, and after COVID-19 pandemic. In order to ascertain the pandemic impact on the company's current ratio, the data calculated in three period: before (2017–2019), during (2020–2021), and after (2022-2024) pandemic. This study uses before pandemic as a baseline by testing 30 data of company financial statements listed on the Indonesia Stock Exchange in 2017-2024. This research tested by regression analysis on historical data using SPSS software to identifies pandemic effect on the resulting current ratio. The result shows that during the pandemic, the decrease of current ratio with a P-value 0,028 have a significant effect compared to before pandemic. Meanwhile, after pandemic shows that the decrease of current ratio is no longer significant with P-value 0.197. Keywords: Current Ratio, Current Assets, Current Liabilities, COVID-19 Pandemic, Liquidity Management.